2003
DOI: 10.1183/09031936.03.00298903
|View full text |Cite
|
Sign up to set email alerts
|

The role of mean inspiratory effort on daytime sleepiness

Abstract: This study has investigated the role of average maximum inspiratory effort in excessive daytime sleepiness in patients with obstructive sleep apnoea syndrome (OSAS) and upper airway resistance syndrome (UARS).Fifteen patients diagnosed with UARS and 32 patients with OSAS, withw5.5 h total sleep time (TST) during 8 h of nocturnal polygraphic recordings, were included in the study. Demographical data, polysomnographical data and data about daytime sleepiness, including Epworth sleepiness scale (ESS) and multiple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
19
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 46 publications
3
19
0
Order By: Relevance
“…In addition, in the eucapnic patients, perturbations in their sleep study results correlated with abnormalities in their WOB. These results are consistent with the findings of Pelin et al [29], who demonstrated a significant correlation between inspiratory effort and daytime sleepiness in OSAS. It appears from our study that the greater workload (both restrictive and elastic) required during sleep of both eucapnic nonobese and obese subjects contributes to their sleep-disordered breathing.…”
Section: Discussionsupporting
confidence: 83%
“…In addition, in the eucapnic patients, perturbations in their sleep study results correlated with abnormalities in their WOB. These results are consistent with the findings of Pelin et al [29], who demonstrated a significant correlation between inspiratory effort and daytime sleepiness in OSAS. It appears from our study that the greater workload (both restrictive and elastic) required during sleep of both eucapnic nonobese and obese subjects contributes to their sleep-disordered breathing.…”
Section: Discussionsupporting
confidence: 83%
“…Our work has the major advantage over previous investigations in that we included patients with a wide spectrum of OSA severity. Previous studies in predominantly severe patients with OSA have reported modest univariate correlations between the non-REM ArTH and the AHI (13,14,20) and other markers of OSA severity including the minimum Sp O 2 and ArI (13) and the ESS (21). Taken together, these findings suggest that the ArTH is strongly related to severity of disease, which is consistent with our physiologic understanding.…”
Section: Original Articlesupporting
confidence: 80%
“…Non-REM and REM ArTHs were strongly correlated (r 2 = 0.81; P , 0.001). On average, the overall ArTH measurements were derived from 3 (2-5) events (arousals) in control subjects and 20 (15)(16)(17)(18)(19)(20)(21)(22)(23)(24) events in the patients with OSA. Figure 2 shows the proportion of control subjects and patients with OSA that had a low overall ArTH; most control subjects had a low ArTH, whereas approximately half of the patients with OSA had a low ArTH (P = 0.005).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…(UARS). 17 ESS was significantly correlated with the average maximum Pes (oesophageal pressure) in both Obstructive sleep apnea syndrome and Upper airway resistance syndrome patients. However, no significant correlation was found between the MSLT score and average Pes in both Obstructive sleep apnea syndrome and Upper airway resistance syndrome patients.…”
Section: Discussionmentioning
confidence: 89%